1984
DOI: 10.1016/0025-5408(84)90129-6
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and electrical properties of a monophasic ZrO2Y2O3Bi2O3 solid electrolyte

Abstract: A preparation method is described of monophasic yttria stabilized zirconia doped with Bi203. This material is prepared from a homogeneous power which, after pressing, is sintered in a Bi203 atmosphere. The resulting ceramic has a composition of 0.78Zr02-0.206 YO1.5-O.O14Bi01. 5. The grain boundaries are enriched with bismuth. A relative density of 95% of the theoretical one is attained at a considerably lower temperature than the bismuth free sample. The electrical conductivities of the monophasic Bi doped and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 11 publications
1
7
0
Order By: Relevance
“…Y 3+ however, has a constant density over the whole structure, which results in a higher Y 3+ /Zr 4+ ratio at the GB itself, with 0.33 averaged over the two GB regions at Zr 4+ valleys as compared to 0.225 in the bulk phase (a segregation factor of 1.47). This is consistent with previous simulations 20 , in which Lee et al obtained a segregation factor of 1.2 in a Σ5(310)/[001] structure with the same doping concentration, and an experimental value of 1.5 as an average value over different GBs 25 .…”
Section: La 3+ Segregationsupporting
confidence: 92%
“…Y 3+ however, has a constant density over the whole structure, which results in a higher Y 3+ /Zr 4+ ratio at the GB itself, with 0.33 averaged over the two GB regions at Zr 4+ valleys as compared to 0.225 in the bulk phase (a segregation factor of 1.47). This is consistent with previous simulations 20 , in which Lee et al obtained a segregation factor of 1.2 in a Σ5(310)/[001] structure with the same doping concentration, and an experimental value of 1.5 as an average value over different GBs 25 .…”
Section: La 3+ Segregationsupporting
confidence: 92%
“…These results are consistent with the XRD analysis results, which all indicate that more yttria (10 mol%) is needed in the system to stabilize zirconia and obtain a uniform, fully stabilized cubic structure. This dense and void-free morphology suggest that adding low-melting Bi 2 O 3 can significantly improve material density and promote grain growth because of introducing the liquid phase sintering effect [9,12,18]. The rounded rather than straight grain boundaries seen in the microstructure can be explained as the results of border infiltration occurring during the liquid sintering process.…”
Section: Resultsmentioning
confidence: 99%
“…Winnubst et al . [18] studied the effects of varying amounts of Bi 2 O 3 on the ionic conductivity of YSZ, but in those studies it was found that the enhancing effect of Bi 2 O 3 on the ionic conductivity of YSZ was very limited. Verkerk et al .…”
Section: Introductionmentioning
confidence: 99%
“…A similar phenomenon was reported for Y 2 O 3doped ZrO 2 . 17,19 In Fig. 4, measured grain size after 1 h of sintering is plotted against sintering temperature.…”
Section: May 2002mentioning
confidence: 99%
“…The distribution of the second phases affects the overall electrical properties of YSZ. 17 There is a lack of data concerning the influence of the addition of Bi 2 O 3 on the properties and structure of Sc 2 O 3 -doped ZrO 2 . Achievement of sufficient conductivity for low-temperature SOFC operation and establishment of a decreased-temperature cofiring schedule for componentsi.e., air electrode, electrolyte, interconnection, and fuel electrodeare desired.…”
Section: Introductionmentioning
confidence: 99%